Evaluación de tres protocolos de reproducción programada en manejo extensivo de la cabra chusca del bosque seco de la provincia de Loja - Tite Bolagay, Santiago Sebastián (2021)
In the dry forest of the province of Loja, which is the place of origin of the Chusca goat, was evaluated the efficiency of three programmed reproduction protocols, There are studies carried out in different breeds of goats and under different management systems, However, there is no information on the application of programmed reproduction methods in the Chusca goat under extensive management in the dry forest, in this way it was possible to observe which of the protocols was more adapted to this breed and with better results. From a group of 21 goats and divided into three subgroups at random, the first treatment consisted in the use of intravaginal sponges, the second treatment consisted in the use of prostaglandins, in the third treatment injectable progesterone was applied, the work was carried out in A period of 113 days from its beginning to its end, for the selection of the UE (Experimental Unit), the females that reached physical and physiological maturity for reproduction were considered, once the experimental groups with 7 UE per treatment were formed. the different heat synchronization protocols were applied. The results allowed us to observe that in the three applied treatments all had as a result the presence of heat in 100%, the period and intensity of each treatment varied among themselves, this has resulted that T2 was the one which presented uniformity in the range of intensity heat rated as Medium with a duration of 14 hours. The return to heat in T3 was 43%, in T1 it was 14%, T2 was the protocol that did not report returns in heat (0%). The pregnancy percentage reached 100% (80-90 days post-treatment by ultrasound), taking into account that the presence of the male after the application of the protocols was permanent. The economic cost per synchronized and pregnant female reported that T1 with a cost of $ 32.21 and T3 $ 22.95, the values presented with an approximate difference of $ 10.00 between them. , T2 being the cheapest of the treatments with a price of $ 8.07. It was possible to determine that all the synchronization treatments gave very good results within the reproductive variables analyzed. All treatments helped to stimulate the restart of reproductive functionality and allow the shortening of open days (birth-conception interval). The T2 treatment based on prostaglandins PGF2a turned out to be the most efficient reproductively and economically. Keywords: Creole goat, heat synchronizatio